Improving the Ability to Read Explanatory Texts with the Discovery Learning Model Assisted by Literacy Tree Media in Grade XI Students - Sarli Sarli; Esti Swatikasari (Journal of General Education and Humanities, 2026)
Low reading comprehension of explanatory texts remains a challenge for high school students in Indonesia, as seen from the results of the 2021 PIRLS. This Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model aims to describe the improvement of the learning process and reading ability of explanatory texts through the Discovery Learning model assisted by the Literacy Tree media in 27 grade XI students of SMA Negeri 1 Nunukan who were selected purposively. Data were collected through comprehension tests, observations, interviews, questionnaires, and documentation, analyzed quantitatively through the average score and percentage of completion (KKM 75), and qualitatively descriptively. The results showed a significant increase from pre-action to Cycle II, with an average score exceeding the KKM, learning completion above 50%, and better ability to identify main ideas, cause-and-effect relationships, process flow, and text conclusions. The conclusion of the study states that Discovery Learning assisted by the Literacy Tree media is effective in improving reading comprehension of explanatory texts and student engagement.